2006
DOI: 10.1111/j.1600-0765.2006.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin levels in gingival crevicular fluid in periodontal health and disease

Abstract: As periodontal tissue destruction increased, there was a substantial decrease in gingival crevicular fluid leptin concentration. This observation extends our knowledge of the protective role of leptin in periodontal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
4
15

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 25 publications
8
80
4
15
Order By: Relevance
“…26 Leptin expression is also seen in pulp samples, and it is found to increase during pulpal inflammation. 27 Recent studies evaluated leptin levels in gingival crevicular fluid during orthodontic tooth movement and found that the leptin level is decreased during orthodontic tooth movement.…”
Section: Introductionmentioning
confidence: 93%
“…26 Leptin expression is also seen in pulp samples, and it is found to increase during pulpal inflammation. 27 Recent studies evaluated leptin levels in gingival crevicular fluid during orthodontic tooth movement and found that the leptin level is decreased during orthodontic tooth movement.…”
Section: Introductionmentioning
confidence: 93%
“…Leptin berasal dari bahasa Yunani Leptos yang berarti kurus. 1,2 Leptin terletak pada kromosom no 7 manusia. 2 Leptin disintesis terutama oleh sel adiposa yang berfungsi sebagai regulasi berat badan, sistem hematopoetik dan remodelling tulang.…”
Section: Pendahuluanunclassified
“…1,2 Leptin terletak pada kromosom no 7 manusia. 2 Leptin disintesis terutama oleh sel adiposa yang berfungsi sebagai regulasi berat badan, sistem hematopoetik dan remodelling tulang. [1][2][3] Reseptor utama leptin berada di hipotalamus, dan berfungsi untuk menghambat asupan makanan seta meningkatkan penggunaan energi.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations